The dynamics of collaboration and knowledge sharing in co-working spaces: The study of Istanbul case - Kozaman Aygun, Senem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
The new working practices, which include individualised and freelance employment options, affected the nature of workspaces and transformed them into more flexible and less dependent on distance and fixed places. Accordingly, co-working spaces (CWSs) are the new platforms that initiate an environment for interaction between different groups or individuals in a community. This research aims to represent the development process and location patterns of CWSs in Istanbul and the dynamics of collaboration and knowledge flow between individuals or firms in CWSs. In this context, 20 semi-structured interviews were conducted with users from different sectors, managers, and founders of spaces. By presenting the results of the in-depth interviews, the research argues that interaction among co-located agents is related to the motivation and the requirement for collaborative action. The willingness and demand for collaboration of co-located agents are especially more prominent in the early stages of a business formation that can result from cost reduction or in the start-ups that are open to new business opportunities and meet investors. The physical environment and social community platforms provided by CWSs can act as an intermediary in the first interaction, yet trust between agents is also crucial for the continuity of knowledge flow that can contribute to innovative processes.
Keywords: co-working space; collaboration; innovation; Istanbul; knowledge flows; COWORKING-SPACES; ENTREPRENEURSHIP; Architecture